Numerical assessment of a hybrid energy generation process and energy storage system based on alkaline fuel cell, solar energy and Stirling engine. (July 2021) - Li, Dezhi; Guo, Jianan; Zhang, Jun; Zhan, Lina; Alizadeh, Mehrsam
Highlights: The performance of the novel energy conversion process based on alkaline fuel cell and solar energy with energy storage option is presented. The waste heat of the fuel cell is used to in the Stirling engine generate further electricity. The total efficiency and total exergy destruction of the system are 63.8 % and 73.01 kW, respectively. The precise adjustment of the pre-set pressure has a key role in the design, sizing and improving the performance of the storage system. Abstract: Today, the use of alternative energy sources such as solar energy to provide the energy demand of human societies is inevitable. In addition, fuel cell systems generate electricity from the energy contained in the fuel. Meanwhile, clean energy-based hybrid energy systems can be a suitable solution for fossil fuels problems. However, for their widespread commercialization, more detailed and powerful studies are needed. On the other hand, in order to achieve sustainable development for the use of renewable energy sources due to their nature, energy storage is required. The aim of this paper is introduce and examine a new energy system operation based on fuel cell technology and solar energy. The novel energy conversion process proposed consisting of two sub-systems, the energy generation and energy storage sub-system. Power generation sub-system includes alkaline fuel cell (AFC), solar photovoltaic (PV) field and electrolyzer as well as Stirling engine and absorption chiller. The second sub-system considered in this paper is energy storage using pumped-hydro-compressed air system (PH-CA). The energy system operation is investigated and discussed under different operating conditions. Results revealed that for a 1 kWel AFC, the Stirling engine and absorption chiller produce 1.27 and 2.48 kW of electricity and cooling load, respectively. Moreover, the system efficiency is 63.8% and 73.01 kW of exergy is destroyed. It was also found that, up to 2.97 kWh of electricity can be stored by the PH-CA storage system. In such a context, the required storage system volume under considered process and conditions was 11.7 m 3 .